Analysis of the social history of music in the renaissance - López Jiménez, Luz Esther; Verdecia Marín, Marleys (Revista Universidad de Guayaquil, 2016)
Presently work is approached an approach on the music's development in the Rebirth like consequence in the new way of life and of the humanistic theories. For he/she is necessary it to detail the different expressions that arise in the musical art from thegeneric ones, music type, composers as well as the development of the polyphony cuin the different schools. For such a reason the content of the article heads to establish relationships before among the elements mentioned.
Keywords: polyphony; composers; goods; schools